Analisis Nilai-Nilai Pendidikan Birrul Walidain dan Takrimul Aulad dalam Film Animasi Nussa dan Rara - Kurniawati, Rita (PT Faliha Cendekia Nusantara, 2024)
This research was conducted to find out what the educational values of Birul Walidain are, the educational characteristics of Takrimul Ulad in the animated film Nussa and Rara which are in accordance with Islamic teachings, as well as the impact of the animated film Nussa and Rara on the people who watch it. This research is a type of documentary research. The presentation of data in this research is qualitative. The data analysis technique used is the Miles and Huberman model, in the form of data collection, data reduction, data presentation and then drawing conclusions. by analyzing the content of the animated film Nussa and Rara first before concluding. The results of the research show that many of the educational values of Birul Walidain and characteristics of Takrimul Ulad education contained in the animated film Nussa and Rara in episodes 10 and 12 are in accordance with Islamic teachings. There are also many positive impacts for people who watch the animated film Nussa and Rara. This rara makes the audience feel that they will not get bored with the scenes shown, because the animated film Nussa and Rara is not just entertainment but can also be used as a guide or reference for learning media for children under the guidance of their parents.